Троя и культуры Нижнего Дуная. Некоторые параллели позднего бронзового века (керамика и орнаментальные стили) - Бруяко, И.В. (Материалы по археологии Северного Причерноморья, 2010)
The excavation of the hillfort of “Kartal” (multilayer site on the Lower Danube) has revealed a cultural layer with archaeological materials of the Early Hallstatt period (the layer “Kartal II”). As a result of excavation there was found a dwelling and different household objects of this period. Additionally, a large collection of handmade pottery was obtained. Two ceramic forms are mainly discussed in the article – amphorae and cups with elbow-like handles. Similar vessels were distributed across the Balkans in the Late Bronze Age and Early Iron Age. Results of analysis demonstrate very large similarities between mentioned ceramic forms from Troia VIIb2 on the one hand, and those from Kartal on the other hand. At the same time, there are some reasons to assume that these types of vessels along with another barbarian fine pottery started to penetrate the Troja region as early as the VIIb1 period. Some arguments pro et contra this hypothesis are considered in the article. The archaeological material from Kartal allows discussing the problem of appearance of the pottery with stamped ornamentation in Troja. It is probable that the model of spread of stamped pottery instead of incised one in strictly successive order in different Balkan regions needs of correction. The elements of imprinted ornamentation appeared as early as the period of existence of cultural groups with incised pottery. It is suggested that the stamped pottery from Troja has to be dated to the VIIb3 level. The article offers cultural-chronological position of the hillfort of “Kartal” among different cultures of the Lower Danube region. It is very probable that the “Kartal II”.